## anonymous one year ago Can someone help me solve this?

1. anonymous

A system of equations is shown below: y = 3x − 7 y = 2x + 1 What is the solution to the system of equations? (8, 17) (−8, 17) (−8, −17) (8, −17)

2. anonymous

I need to know how to do this concept later for a test.

3. anonymous

@Abhisar @BOOKER23

4. anonymous

@darkb0nebeauty

5. butterflydreamer

|dw:1433427892039:dw| simplify this.

6. anonymous

Then what @butterflydreamer

7. butterflydreamer

did you simplify it?

8. anonymous

how do you do that ? @butterflydreamer

9. butterflydreamer

what does 3x - 7 + 7 equal to?

10. butterflydreamer

The -7 + 7 will cancel out.. so you're left with just 3x so we know |dw:1433428826676:dw| Now what does 1 + 7 = ?

11. anonymous

8 @butterflydreamer

12. butterflydreamer

yes so now we have: |dw:1433428973058:dw| Now what does: 3x - 2x = ?

13. anonymous

1x?

14. butterflydreamer

yes exactly :) so : |dw:1433429128261:dw| Now that we know x = 8.. we need to find out what y equals to... To do this plug x = 8 into one of the original equations |dw:1433429158638:dw|

15. butterflydreamer

So if we use the equation y = 2x +1 and we plug in x = 8 we will get: y = 2x + 1 y = 2(8) + 1 y = ?

16. anonymous

um

17. anonymous

17?

18. butterflydreamer

yeeeess!!! y = 17 SO to sum it up x = 8 , y = 17 And we're done :) Now put it in the form (x, y ) ---> (8, 17)

19. anonymous

great.

20. anonymous

Can you help me out with one more thing @butterflydreamer

21. butterflydreamer

i would love to but it's actually time for me to go to bed LOl. Sorry! Good luck :)!

22. dmndlife24

bed?? It's like 11 in the morning over here lol